MANAJEMEN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU - NURHAKIM WARAS (UNISAN JURNAL, 2024)
The focus of this research is the management of Principal Teachers at SDIT Imam Syafi’i Petanahan Kebumen. The sub focus is discipline, responsibility. The purpose of this research is to find out. This type of research is a qualitative descriptive research, namely a research procedure that produces descriptive data in the form of written or spoken words from the people and actors observed, directed from the background of the individual as a whole (holistic) without isolating individuals and their organizations in variables but looking at them. as part of a whole. In data collection techniques in this study used various techniques, namely interviews, observation and documentation. The data analysis procedure used in this research is qualitative analysis. the teacher, information was obtained that after receiving guidance and direction from the Head of SDIT Imam Syafi’i Kecamatan Petanahan Kabupaten Kebumen it turned out that the teacher’s ability was much better than before.